2021
DOI: 10.1016/j.invent.2021.100410
|View full text |Cite
|
Sign up to set email alerts
|

An emotion-based online intervention for reducing anxiety and depression in cancer patients: Study protocol for a randomized controlled trial

Abstract: Background A cancer diagnosis can cause severe emotional distress and affect quality of life as well as social relationships. The transition from inpatient to outpatient treatment is burdened by stressful uncertainties and a gap of psycho-oncological care. In addition, further barriers, such as information deficits or fear of stigmatization, might hinder cancer patients to use psycho-oncological face-to-face interventions. Online interventions can be a low-threshold adjunct to existing face-to-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Early intervention of patients with negative mood disorders in families with cancer is helpful to promote the prognosis and life quality of cancer patients [ 2 ]. The study found that the social concern of emotional disorders of cancer patients and their families is incomplete, lack of multidimensional longitudinal evaluation, establish the integration of hospital, community follow-up and Internet follow-up mechanism, determine the target population, and analyze the influencing factors in real time [ 3 ]. Achieve individual transmission analysis, specify blocking intervention measures.…”
Section: Introductionmentioning
confidence: 99%
“…Early intervention of patients with negative mood disorders in families with cancer is helpful to promote the prognosis and life quality of cancer patients [ 2 ]. The study found that the social concern of emotional disorders of cancer patients and their families is incomplete, lack of multidimensional longitudinal evaluation, establish the integration of hospital, community follow-up and Internet follow-up mechanism, determine the target population, and analyze the influencing factors in real time [ 3 ]. Achieve individual transmission analysis, specify blocking intervention measures.…”
Section: Introductionmentioning
confidence: 99%
“…This result may be due to elderly people being interested in an attending training programs to overcome their feelings of depression by using different strategies to deal with this symptom such as positive thinking, self-awareness, and stress management. This result was supported by Tsiouris, et al, (2021) (22) studied the emotion-primarily based intervention for reducing anxiety and melancholy in elderly sufferers and observed that majority of aged human beings had improvement in despair for elderly patients. Conversely, this result turned into congruent with Douki, et al, (2019) (11) who studied the effectiveness of ne thinking education on anxiety, despair, and best of life of elderly people, and discovered that there may be relatively statistically vast development in overall depression level in the post-intervention segment.…”
Section: Discussionmentioning
confidence: 76%
“…One point for each correct answer. The correct answer is yes for questions number (2,3,4,6,8,10,11,12,13,14,16,17,18,20,22,23,24,25) and the correct answer is no for questions number (1,5,7,9,15,19,21). The correct answer was scored 1 and the wrong answer was scored 0.…”
Section: Scoring Systemmentioning
confidence: 99%
“…On average, users are expected to spend approximately 30 to 60 minutes on each unit. Detailed information on the study design of the RCT has been provided elsewhere [ 22 ].…”
Section: Methodsmentioning
confidence: 99%